Enhanced waterproof performance of superhydrophobic SiO2/PDMS coating - He, Shuhao; Chen, Jingran; Lu, Yao; Huang, Shuai; Feng, Kai (Progress in organic coatings, 2024)
Superhydrophobic coatings are renowned for their exceptional wetting properties and exhibit superior characteristics including waterproofing, self-cleaning, anti-fogging, anti-icing, corrosion resistance, and drag reduction. These qualities have led to their widespread application in fields such as biomedical engineering, new energy, electronic devices, aerospace, and marine engineering. However, the complexity of the fabrication processes for these coatings, along with their limited applicability and the absence of systematic methods to evaluate waterproof performance, restricts broad industrial-scale implementation. In this study, a dispersion containing hydrophobic silica (SiO2) nanoparticles and polydimethylsiloxane (PDMS) was prepared using a blend dispersion method. Using a spraying technique, a uniform superhydrophobic SiO2/PDMS coating was successfully applied to various substrates, demonstrating excellent adaptability across different base materials. To systematically investigate the waterproofing capabilities of this coating, this study has introduced a comprehensive evaluation methodology encompassing coating stability (thermal, chemical, and environmental stability), water resistance properties (dynamic and static water environments), anti-permeation performance (static hydraulic pressure and dynamic water flow), and durability of electronic devices in water environments (water immersion and water flow impact). The results indicate that optimal fabrication parameters include a SiO2 particle size of 20 nm, a concentration of 4 wt%, and a PDMS-to-SiO2 ratio of 1:1, with four application layers. The coating demonstrates robust stability under high and low temperatures, as well as in chemical and environmental conditions. Waterproof performance tests reveal that the contact angle remains above 150° in both dynamic water environments and static water immersion, significantly reducing water absorption and permeation, thus enhancing waterproof efficiency. The efficacy of the developed coating is further evidenced by tests on commercially available electronic timers and a bespoke LED flash circuit component, where the lifespan of electronic devices in immersion and dynamic impact water environments increased by 105 and 65 times, respectively. [Display omitted] •Uniform superhydrophobic SiO2/PDMS coating applied across diverse substrates via spraying, showing excellent adaptability•Introduced a comprehensive method to evaluate coating stability and waterproof effectiveness•Maintained a contact angle above 150°, greatly enhancing waterproof efficiency•Significantly extended the lifespan of electronic devices in water environments by up to 105 times